2015
DOI: 10.1155/2015/385428
|View full text |Cite
|
Sign up to set email alerts
|

T1Relaxation Measurement ofEx-VivoBreast Cancer Tissues at Ultralow Magnetic Fields

Abstract: We investigated T 1 relaxations of ex-vivo cancer tissues at low magnetic fields in order to check the possibility of achieving a T 1 contrast higher than those obtained at high fields. The T 1 relaxations of fifteen pairs (normal and cancerous) of breast tissue samples were measured at three magnetic fields, 37, 62, and 122 μT, using our superconducting quantum interference device-based ultralow field nuclear magnetic resonance setup, optimally developed for ex-vivo tissue studies. A signal reconstruction bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, the ULF MRI approach may provide open MRI systems for airport security [11], emergency rooms, and field hospitals [20,25], and it can also be combined with magnetoencephalography (MEG) for recording both anatomical and functional (biomagnetic) information about the brain [23,24]. Moreover, the unique advantage of ULF MRI is the higher T 1 -contrast in low-field MRI which has been proposed for the discrimination of tissue [35][36][37]. is Concepts in Magnetic Resonance Part B, Magnetic Resonance Engineering enhanced T 1 -contrast is a prospective supplement to highfield MRI in pathology studies using the SQUID-based ULF MRI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ULF MRI approach may provide open MRI systems for airport security [11], emergency rooms, and field hospitals [20,25], and it can also be combined with magnetoencephalography (MEG) for recording both anatomical and functional (biomagnetic) information about the brain [23,24]. Moreover, the unique advantage of ULF MRI is the higher T 1 -contrast in low-field MRI which has been proposed for the discrimination of tissue [35][36][37]. is Concepts in Magnetic Resonance Part B, Magnetic Resonance Engineering enhanced T 1 -contrast is a prospective supplement to highfield MRI in pathology studies using the SQUID-based ULF MRI.…”
Section: Discussionmentioning
confidence: 99%
“…As a step toward developing clinical methods, it would be advantageous to estimate the sensitivity and specificity of ULF‐MRI to molecular processes likely to be found in pathology, and to quantify relaxation times pertinent to image contrast. For example, studies of excised specimens have demonstrated that ULF relaxation times can differentiate tumors from normal tissues .…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a stronger B p , various types of B p coils have been used, such as a permanent magnet 1 and coils with the following cooling agents: forced air, 2 water, 3,4 a fluorine-based industrial coolant, 5 liquid helium, 6,7 and liquid nitrogen. [8][9][10][11][12] In spite of these efforts, the strength of B p has been limited to below approximately 150 mT. 3 Increasing the magnitude of the B p has also yielded unwanted effects: flux trapping in the superconducting pickup coil 7 and the generation of eddy currents on the walls of a magnetically shielded room (MSR).…”
mentioning
confidence: 99%
“…Currently, a strong pre-polarization field (B p ) is indispensable for increasing the signal-to-noise ratio (SNR) in most superconducting quantum interference device (SQUID)-based ultra-low field (ULF) nuclear magnetic resonance (NMR)/magnetic resonance imaging (MRI) studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The field should be applied for a while before acquisition, because a static magnetic field (B m ) operating in the micro-tesla range cannot generate sufficient nuclear spin polarization. There are some challenges involved in producing a strong B p , which is one of the critical issues in ULF-NMR/MRI.…”
mentioning
confidence: 99%